Retention rate of biologic and targeted synthetic anti-rheumatic drugs in elderly rheumatoid arthritis patients: data from GISEA registry - Manfredi, Andreina; Fornaro, Marco; Bazzani, Chiara; Perniola, Simone; Cauli, Alberto; Rai, Alessandra; Favalli, Ennio Giulio; Bugatti, Serena; Rossini, Maurizio; Foti, Rosario; Conti, Fabrizio; Lopalco, Giuseppe; et al. (Frontiers in Medicine, 2024)
Objectives An increased number of elderly individuals affected by rheumatoid arthritis (RA) has been reported, including both patients with RA onset in advanced age and patients aged with the disease. In this registry-based study, we aimed to analyze the retention rate and cause of discontinuation of biologic (b) and targeted synthetic (ts)-disease-modifying anti-rheumatic drugs (DMARDs) in RA patients over 65 year old. Methods RA patients enrolled in the Italian GISEA registry and starting a b- or a ts-DMARD over 65 years of age were included. Demographic, clinical, serologic, and therapeutic features were collected. Results A total of 1,221 elderly RA patients were analyzed (mean age 71.6 ± 5.2 years). RA was diagnosed before 65 years in 72.5% of cases, a 60.6% of patients experienced a previous b- or ts-DMARD. In patients older than 65 initiating a new b- or ts-DMARDS, tumor necrosis factor alpha inhibitors (TNFi) were prescribed in 29.6% of patients, abatacept in 24.8%, anti-interleukin 6 receptor antagonists (anti-IL6R) in 16.3%, Janus kinases inhibitors (JAKi) in 24.9%, and rituximab in 4.4%. The main causes of discontinuation were primary or secondary inadequate responses (66.1%). The median retention rate for all treatments was 181.3 weeks. A statistically higher retention rate was observed for abatacept when compared to TNFi (p = 0.02), JAKi (p < 0.001), and anti-IL6R (p < 0.001), and for TNFi vs. JAKi (p = 0.013). Conclusion We described, in a real-life setting, elderly RA patients treated with a biologic or a ts-DMARD in Italy. Loss of efficacy was the main cause of discontinuation, and the DMARD safety profile suggests that age does not contraindicate their use. Our study reinforced that the control of disease activity is mandatory.